2000
DOI: 10.1144/jgs.157.3.615
|View full text |Cite
|
Sign up to set email alerts
|

Late Proterozoic extensional collapse in the Arabian–Nubian Shield

Abstract: A structural and petrological study of the Late Proterozoic rocks in the Wadi Kid area, Sinai, Egypt indicates the presence of an extensional metamorphic core complex in the northern Arabian-Nubian Shield. Gneissic domes throughout the Arabian-Nubian Shield resemble the core complex of the Wadi Kid area and as a result, they are interpreted as extensional metamorphic core complexes. The presence of a widespread phase of extension at the end of the Pan-African period in the Arabian-Nubian Shield requires a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
119
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(127 citation statements)
references
References 66 publications
7
119
1
Order By: Relevance
“…Jacobs et al (2003) reported Pan-African extensional structures in the Wohlthatmassiv of central Dronning Maud Land (12 • E) and suggested that orogenic collapse had occurred. Late Pan-African extension is also reported from the East African orogen of Madagascar (Collins, Razakamanana & Windley, 2000;De Wit et al 2001) and in the Arabian-Nubian Shield in Egypt (Blasband et al 2000).…”
Section: B Late-orogenic Collapse Of the Pan-african East Antarctimentioning
confidence: 73%
“…Jacobs et al (2003) reported Pan-African extensional structures in the Wohlthatmassiv of central Dronning Maud Land (12 • E) and suggested that orogenic collapse had occurred. Late Pan-African extension is also reported from the East African orogen of Madagascar (Collins, Razakamanana & Windley, 2000;De Wit et al 2001) and in the Arabian-Nubian Shield in Egypt (Blasband et al 2000).…”
Section: B Late-orogenic Collapse Of the Pan-african East Antarctimentioning
confidence: 73%
“…This transpression was accommodated by left-lateral strikeslip displacements along the brittle-ductile Wadera Shear Zone and gently dipping shear surfaces at conjugate sets of shear zones (Yihunie and Tesfaye 1998). Low-angle strike-slip shears/faults associated with the late Proterozoic extensional tectonic regime in the Neoproterozoic Arabian-Nubian Shield were reported from Wadi Kid (Blasband et al 2000) and Elat areas, Sinai (Garfunkel 1999) and from central Madagascar (Collins et al 2000), and were interpreted to have been developed under an extensional tectonic regime. These authors further suggested a change in the tectonic regime from compressional setting to extensional and orogenic collapse along the East African Orogen during the late Proterozoic.…”
Section: Discussionmentioning
confidence: 99%
“…Paleogeographic reconstructions suggest a close link between India and Madagascar from the late Neoproterozoic/early Paleozoic (McWilliams 1981;Stern 1994;Meert et al 1995;Blasband et al 2000;De Wit 2003;Sommer et al 2003;Veevers 2004;Collins and Pisarevsky 2005;Ratheesh Kumar et al 2014) until their separation in the late Cretaceous (Storey et al 1995;Torsvik et al 1998Torsvik et al , 2000 fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…1). The present-day crystalline basement of Madagascar is made up of Archean to Neoproterozoic crustal units with equivalents in India and East Africa (Stern 1994;Unrug 1996;Blasband et al 2000;Kröner et al 2000;Veevers 2004;Collins and Pisarevsky 2005). The Antongil-Masora Block of Madagascar can be correlated with the Western Dharwar Craton (WDC) of India on the basis of the coherent Paleo/Mesoarchean and Neoarchean evolutionary histories of the two crustal units (e.g., Tucker et al 1999bTucker et al , 2011aTucker et al , 2011bTucker et al , 2014Schofield et al 2010;Rekha et al 2013;.…”
Section: Introductionmentioning
confidence: 99%